Efficient heterogeneous catalytic system for chemoselective hydrogenation of unsaturated ketones in aqueous medium - Deshmukh, Amit A.; Kinage, Anil K.; Kumar, Rajiv; Meijboom, Reinout (Polyhedron, 2010)
A highly chemoselective and green heterogeneous catalytic system of immobilized Ru(II)-phenanthroline complexes on amino functionalised MCM-41 material for the chemoselective hydrogenation of unsaturated ketones to unsaturated alcohols is demonstrated using water as a solvent The XRD and FTIR spectra show the highly ordered hexagonal nature of the MCM-41 even after encapsulation of the ruthenium complex The complex retains its configuration after anchoring as was confirmed by FTIR and UV-Vis analysis The detailed reaction parametric effect was studied for the hydrogenation of 3 methylpent-3-en-2-one to achieve complete conversion up to >99% chemoselectivity of 3-methylpent-3-en-2 ol The anchored heterogeneous catalysts were recycled effectively and reused five times with marginal changes in activity and selectivity The use of water as a solvent not only afforded high activity for the hydroge nation reaction compared to organic solvents but also afforded a green process Crown Copyright (C) 2010 Published by Elsevier Ltd All rights reserved
Keywords: 1 10 Phenanthroline; alpha beta Unsaturated ketone; Chemoselective hydrogenation; mesoporous materials; ruthenium